Biocompatibility of Poly[di(carboxylatophenoxy)-phosphazene] Polymer: In Vitro Cytotoxicity in Cell Culture - Ustun-Karatop, Eslin; Cakir-Koc, Rabia (SPRINGER, 2022)
Purpose Polyphosphazenes are synthetic polymers that contain phosphate-nitrogen molecules. Polyphosphazene's inorganic main structure is capable of hydrolytic degradation and modulated by choosing the relevant side group. Poly[di(carboxylatophenoxy)-phosphazene (PCPP) is a polymer that is preferred due to its macromolecular structure, excellent film-forming, and microcapsule forming ability. It has biological activity when used with antigenic proteins of bacteria and viruses as microcapsule forms. Sodium chloride is added to the solution of the PCPP polymer to create coacervate microdroplets. These microdroplets are stabilized by cross-linking by adding calcium ions. PCPP is known as a biocompatible polymer; however, there are no studies on the cytotoxicity of the microparticle or water-soluble form of the PCPP. Methods To show the compatibility of PCPP on cell culture, different concentrations of PCPP's cytotoxic effect were investigated. The microparticle form of PCPP polymer was obtained by the coacervation method. The size of these microcapsules was shown by the dynamic light scattering. Also, the cytotoxicity of PCPP microparticles and PCPP polymer in different concentrations were examined using mouse fibroblast cell lines by XTT assay. The number of cells undergoing apoptosis was determined by the DAPI staining assay. Concentration-dependent cytotoxicity was shown by this study. Results PCPP microparticles and soluble form of this polymer have shown no toxic effects in studied concentrations. The average size range of the PCPP microparticles was found to be 2828 mu m. This study also showed that, when ISO standards are referenced, both soluble and microparticle form of the PCPPdid not demonstrate any toxic effect on the L929 cell line. Conclusions PCPP is not toxic at the concentrations studied in in vitro cell culture and supports the literature regarding its biocompatibility.
Keywords: PCPP; Polyphozphane; Microparticle; Cytotoxicity; Biocompatible; POLYPHOSPHAZENES; MICROSPHERES; ADJUVANT; Pharmacology & Pharmacy